Pembelajaran Penyakit Terkait Perilaku, Merokok, dan Edukasi untuk Berhenti Merokok di Pendidikan Dokter Fakultas Kedokteran UGM - Yayi Suryo Prabandari (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2014)
Background: As the third big populous smoker country in the world, smoking-related diseases have become a major cause of death in Indonesia. Physician should play role in preventing tobacco epidemic. Therefore, the medical curriculum should prepare graduates who will be competent to explain the health effects of smoking behavior and help patients quit smoking. This study proposed to describe how far tobacco and smoking topic were thought in the medical school curriculum and assess student attitudes toward the necessity of physicians to routinely asked on smoking behavior, advice patients to stop smoking as well as the important of physician to receive smoking related diseases education in medical school.Method: The study was based on five separate cross sectional surveys carried out in 200, 2007, 2009, 2010 and 2011. Participants were 1696 students (733 males and 963 females) of Faculty of Medicine, Universitas Gadjah Mada (FM UGM). They were the Non- Problem Based Learning Curriculum (N-PBLC), the PBL Curriculum (PBL-C) and the Competency Based Curriculum (CBC) batches. Data was collected through a self-administered questionnaire. Descriptive analysis was used to present the data.Results: Cigarettes smoking topic had been delivered in FM UGM by several lectures (N-PBLC students) and blocks (the PBL-C and the CBC students). The amount of 40,6 % to 83,5 % students in 5 years surveys reported that they had been trained on subjects that discussed the cigarette smoking topic. Topics on how to help quit smoking reported lower (12,3%-50%) than topic of tobacco related diseases or tobacco and public health. The majority of students mentioned that doctors should ask and give advice or patient’ education (96,7 % - 99,8 %). More than 95 % of students stated that the teaching that addresses cigarette smoking related diseases is important to be taught and trained in medical school.Conclusion: Teaching and learning on the subject of cigarette smoking related diseases have been given, but needs to be improved, particularly on skills to help patients quit smoking.